The influence of daily meteorology on boreal fire emissions and regional trace gas variability. Issue 11 (18th November 2016) - Wiggins, E. B.; Veraverbeke, S.; Henderson, J. M.; Karion, A.; Miller, J. B.; Lindaas, J.; Commane, R.; Sweeney, C.; Luus, K. A.; Tosca, M. G.; Dinardo, S. J.; Wofsy, S.; et al.
Abstract: Relationships between boreal wildfire emissions and day‐to‐day variations in meteorological variables are complex and have important implications for the sensitivity of high‐latitude ecosystems to climate change. We examined the influence of environmental conditions on boreal fire emissions and fire contributions to regional trace gas variability in interior Alaska during the summer of 2013 using two types of analysis. First, we quantified the degree to which meteorological and fire weather indices explained regional variability in fire activity using four different products, including active fires, fire radiative power, burned area, and carbon emissions. Second, we combined daily emissions from the Alaskan Fire Emissions Database (AKFED) with the coupled Polar Weather Research and Forecasting/Stochastic Time‐Inverted Lagrangian Transport model to estimate fire contributions to trace gas concentration measurements at the Carbon in Arctic Reservoirs Vulnerability Experiment‐NOAA Global Monitoring Division (CRV) tower in interior Alaska. Tower observations during two high fire periods were used to estimate CO and CH4 emission factors. We found that vapor pressure deficit and temperature had a level of performance similar to more complex fire weather indices. Emission factors derived from CRV tower measurements were 134 ± 25 g CO per kg of combusted biomass and 7.74 ± 1.06 g CH4 per kg of combusted biomass. Predicted daily CO mole fractions from AKFED emissions were moderately correlated with CRV observations ( r  = 0.68) and had a high bias. The modeling system developed here allows for attribution of emission factors to individual fires and has the potential to improve our understanding of regional CO, CH4, and CO2 budgets. Key Points: Vapor pressure deficit explained fire variability at a level similar to fire weather indexes Tower CO, CH4, and CO2 measurements were used to determine fire emission factors The modeling system we developed may provide insight about emissions from individual Alaskan fires